Possibilities of Using the MSELS Scale for Environmental Literacy Testing in Czech Primary Schools - Svobodová, Silvie; Kroufek, Roman (Scientia in educatione, 2018)
The paper presents the results of an experiment which sought to verify the usability of the MSELS (Middle School Environmental Literacy Survey) research tool in Czech primary schools. Selected psychometric properties of the scale were tested as a complex unit and also within individual segments. The findings were compared with the results of the first usage of the tool during a nationwide research of environmental literacy performed in the USA (McBeth & Volk, 2010; McBeth et al., 2011), which involved sixth- and eighthgraders. The target group for the research presented in this paper were pupils in sixth through ninth grades attending primary schools in the Žatec region. Evidence for the validity of the interpretation of the data obtained was discussed in all areas recommended by the Standards of Educational and Psychological Testing (AERA, APA & NCME, 2014). In most cases, a satisfactory set of evidence was produced to support the use of the scale for the benefit of pupils attending 5th–8th grades of a primary school. The reliability of the attitude scales, actions and sensitivity, documented by the coefficients of their internal consistency, was within acceptable values (α > 0.75), which is why the scales may be recommended for conducting research. The knowledge scale, on the other hand, indicated low reliability (α = 0.55). Its applicability is still possible, yet the data must be interpreted carefully with respect to their reliability.